IMPLEMENTATION OF THE RIGHT TO BE FORGOTTEN AS LEGAL PROTECTION FOR VICTIMS OF NON-CONSENSUAL INTIMATE IMAGES (NCII) IN GENDER-BASED CYBER VIOLENCE (GBCV) - Dyaksha Faisheila Nurdianty (Universitas Negeri Semarang, 2024)
The increasing cases of gender-based cyber violence in Indonesia, particularly the dissemination of Non-Consensual Intimate Images (NCII), have caused serious harm to victims. The Right to Be Forgotten serves as a right for victims to request the removal of harmful content from digital platforms. This study reveals that (1). The rights of NCII victims as part of GBCV have been implemented by law enforcement agencies, especially in fulfilling victims' psychological rights. However, better synergy among relevant institutions is still needed.(2) The application of the Right to Be Forgotten in Indonesia has been carried out through requests either via the Ministry of Communication and Information Technology (Kominfo) or directly to Electronic System Providers (ESPs). (3)The ideal reformulation of the Right to Be Forgotten policy in Indonesia must consider legal, technological, and social aspects to create effective protection for privacy rights in cyberspace. The conclusions are as follows: (1) The implementation of NCII victims' rights has been conducted by law enforcement agencies, particularly in fulfilling victims' psychological needs. Nevertheless, better coordination among institutions is essential to improve supervision and ensure the fulfillment of victims' rights. (2) There is still a lack of transparency and dissemination from ESPs regarding content removal policies. (3) The policy reformulation aims to refine the legal framework, expand implementation coverage, and ensure a balance between individual privacy protection and freedom of information. Recommendations from this study include: (1) Building multi-sectoral coordination to establish a system of checks and balances in the prevention, protection, handling, and recovery of victims of gender-based cyber violence. (2) Enhancing transparency regarding the mechanisms of the Right to Be Forgotten by ESPs and increasing public outreach and education efforts.